Identification of Methods in Developing Basic Social Studies Learning Materials Based on Culture in the Midst of the Issue of Artificial Intelligence Development - Agustin, Nurul; Muhammad Lukman Haris Firmansah (Antroposen: Journal of Social Studies and Humaniora, 2024)
The development of  Learning Materials  itself as a benchmark for lecturers' mastery of the material in the higher education curriculum. Various media can be utilized in the development of  Learning Materials  to ensure the presentation of information that is enjoyable and meaningful. Historical review has proven that existing and developed  Learning Materials  are very useful in the lives of students, but when reviewing the standard education based outcome (OBE) which is correlated with the standard of graduate competency, it is still considered necessary to develop  Learning Materials  in every educational institution or university. Judging from the study that was conducted, this research is a qualitative research with a phenomenological type. Phenomenology is also a philosophical approach to investigating human experience. In this study, researchers are required to develop  Learning Materials  from the results of investigations into  Learning Materials  that have been developed by previous experts. The results of phenomenological research show that the delivery of messages and ideas in  Learning Materials  must be designed based on the subjective experiences of students. Narrative, dialogical, visualization, reflective, experiential, and technology-based approaches have proven effective in creating meaningful learning.